2000
DOI: 10.1590/s0101-81752000000100015
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of the proventriculus of Gryllus assimilis Fabricius (Orthoptera, Gryllidae)

Abstract: ABSTRACT. The proventriculus morphology of the cricket G/y//us assimilis Fabricius, 1775 is described using scanning electron microscopy and the con'elation ofthis structure with the feeding habits briefly considered.KEY WORDS. Orthoptera, Glyllidae, Gry//us, proventriculus ln general, the digestive tube ofthe insects can be divided into three areas: the foregut or stomodeum, the midgut or ventriculus and the hindgut or proctodeum. Its morphological diversity has lead several authors to use it as a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The morphology of the digestive tract and its relation to feeding habits have been studied to a lesser extent than the mouthparts. Comparative studies of the functional morphology of arthropods' digestive apparatus include coleopterans (66,114), orthopterans (65,124), soil-dwelling insects (73), and a number of mite orders (6,52). Generally, carnivorous arthropods have a more chitinized and toothed armature in the foregut and a simpler, shorter, and less differentiated midgut in comparison with herbivorous species.…”
Section: Morphological Traitsmentioning
confidence: 99%
“…The morphology of the digestive tract and its relation to feeding habits have been studied to a lesser extent than the mouthparts. Comparative studies of the functional morphology of arthropods' digestive apparatus include coleopterans (66,114), orthopterans (65,124), soil-dwelling insects (73), and a number of mite orders (6,52). Generally, carnivorous arthropods have a more chitinized and toothed armature in the foregut and a simpler, shorter, and less differentiated midgut in comparison with herbivorous species.…”
Section: Morphological Traitsmentioning
confidence: 99%
“…Parts of the foregut show slight differences within the Orthoptera species. For example, in many Orthoptera species such as Endecous itatibensis Rehn, 1918 (Orthoptera, Gryllidae), Endecous cavernicolus Costa Lima, 1940 (Orthoptera, Gryllidae), Endecous betariensis Mello and Pellegatti-Franco, 1998 (Orthoptera, Gryllidae), (Fontanetti et al, 2002), Isopsera nigroantennata Xia and Liu, 1992 (Orthoptera, Tettigoniidae) (Li & Zheng, 2007), Gryllus assimilis (Fabricius, 1775) (Orthoptera, Gryllidae) (Fontanetti & Zefa, 2000), Gryllus bimaculatus De Geer, 1773 (Orthoptera, Gryllidae) (Woodring & Lorenz, 2007), and Poecilimon cervus Karaba g, 1950 (Orthoptera, Tettigoniidae) (Polat, 2016) the foregut is divided into pharynx, esophagus, crop, and proventriculus. Hochuli et al (1994) (Ayvalı, 1988;Ferreira et al, 1990;Hochuli et al, 1994;Li & Zheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2012) studied the proventricular structures of 20 species from three different subfamilies of the Tettigoniidae family and their basic morphology shows that the proventriculus is composed of six longitudinal folds with highly sclerotized teeth. Li, Ren, Zou, Zhang, and Wang (2011) (Çakıcı & Ergen, 2012;Fontanetti & Zefa, 2000;Li et al, 2011;Li & Zheng, 2007;Szinwelski et al, 2009;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proventriculus is comprised of several sclerotized plates (Chapman 1998), whose structure has been adaptively associated with insect diet (Caetano 1988, Bland & Rentz 1991. Moreover, many studies have shown that the morphol-ogy of proventriculus can provide useful taxonomic characters for Orthoptera (Judd 1948, Bland & Rentz 1991, Fontanetti & Zefa 2000, Fontanetti et al 2002, Coleoptera (Judd 1947, Yahiro 1990), Isoptera (Lebrun 1985), Trichoptera (Gibbs 1967) and Hymenoptera (Roche & Wheeler 1997, Serrão 2001, 2005, 2007. According to a new updated file of orthopteran species, there are more than 6,000 described Tettigonioidae species in the world (Eades et al 2012), and there are more than 300 species of Tettigoniidae in China (Li & Ren 2007), How-ever, the inner structures of the proventriculus and the alimentary canal as a whole are still poorly known in Tettigonioidea.…”
Section: Introductionmentioning
confidence: 99%